2011
DOI: 10.1086/661749
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Developmental Patterns and Energy Expenditure Are Affected by Incubation Temperature in Wood Ducks (Aix sponsa)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press ABSTRACTRecent research in birds has demonstrated that incubation temperature influences a suite of traits important for hatchling development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 25 publications
(46 reference statements)
2
50
0
Order By: Relevance
“…Conversely, low incubation temperature raises energy expenditure during development. In wood ducks for instance, total energy expenditure was similar among low, medium and high incubation temperature groups before the start of pipping; however, between pipping and hatching, embryos from the low-temperature group consumed more energy than those from the high and medium groups (DuRant et al, 2011). Olson et al (2006) found that periodic cooling during the incubation period resulted in lighter embryos and less yolk reserve on embryonic day 12.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Conversely, low incubation temperature raises energy expenditure during development. In wood ducks for instance, total energy expenditure was similar among low, medium and high incubation temperature groups before the start of pipping; however, between pipping and hatching, embryos from the low-temperature group consumed more energy than those from the high and medium groups (DuRant et al, 2011). Olson et al (2006) found that periodic cooling during the incubation period resulted in lighter embryos and less yolk reserve on embryonic day 12.…”
Section: Discussionmentioning
confidence: 98%
“…In precocial wood ducks, hatchling M b decreased with decreasing incubation temperature (Hepp et al, 2006, but also see DuRant et al, 2010). This is due to the increased energy expenditure during embryonic development at low incubation temperature (DuRant et al, 2011). In altricial zebra finches, periodic cooling to 20°C as opposed to constant incubation temperature of 37.5°C reduced M b on embryonic day 12 without an impact on body size (Olson et al, 2006(Olson et al, , 2008.…”
Section: High-temperature Males Weigh Less Throughout Their Livesmentioning
confidence: 95%
See 1 more Smart Citation
“…Consistent with this hypothesis, ducklings with low T 3 hatched later with larger structural size, but in lower body condition, than their counterparts from the high incubation temperature. This suite of effects is attributable to the more protracted growth period associated with slower development at low temperatures [2,4]. In addition, some of the effects of incubation temperature on phenotype appear to attenuate with age [1,7], which could correspond with the convergence of duckling plasma T 3 concentration among incubation temperatures by day 4.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones continue to facilitate development post-hatch, influencing the critical transition to homeothermy, and stimulating immune cell proliferation, feeding and metabolism [10,11]. As thyroid hormones are integral to the above processes, many of which are influenced by incubation temperature [1][2][3][4]8], we hypothesized that the phenotypic effects of embryonic incubation temperature are mediated in part by thyroid hormones. Thus, we predicted that (i) ecologically relevant variation in incubation temperature would positively correlate with thyroid hormone concentrations of nestlings and (ii) thyroid hormones would positively correlate with nestling mass, body condition and incubation period, but negatively correlate with tarsus length because of protracted development [2,4].…”
Section: Introductionmentioning
confidence: 99%